2022
DOI: 10.1111/jfb.15288
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive biology, length‐weight relationship and diet of co‐occurring butterfly rays, Gymnura poecilura and Gymnura zonura, in Malaysian waters

Abstract: Recent IUCN assessments had resulted in up listing of the status of butterfly rays due to concerns of overfishing, but inadequate biological understanding of these rays prevents meaningful conservation and management measures. Therefore, this study was undertaken to address knowledge gaps in the reproductive biology and diet of longtail butterfly ray (Gymnura poecilura) and zone tail butterfly ray (Gymnura zonura) in Malaysian waters. From surveys of landing sites and fish markets from years 2017 to 2022, size… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…In contrast, the DW 50 of the females of U. rogersi was larger than that of males, which coincides with reports from Mejía‐Falla et al (2012). This pattern in many species of elasmobranchs may be in part explained by the need for females to attain a larger size to support pups (Cortés, 2000, 2004; Leung et al, 2023). However, this pattern was not evidenced in U. maculatus , probably due to the small size of this species (Pollom et al, 2020), which has also been suggested for some species of rays like the zipper sand skate Psammobatis extenta (Garman 1913) and the Venezuela round stingray Urotrygon venezuelae Schultz 1949 (Acevedo et al, 2015; Braccini & Chiaramonte, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the DW 50 of the females of U. rogersi was larger than that of males, which coincides with reports from Mejía‐Falla et al (2012). This pattern in many species of elasmobranchs may be in part explained by the need for females to attain a larger size to support pups (Cortés, 2000, 2004; Leung et al, 2023). However, this pattern was not evidenced in U. maculatus , probably due to the small size of this species (Pollom et al, 2020), which has also been suggested for some species of rays like the zipper sand skate Psammobatis extenta (Garman 1913) and the Venezuela round stingray Urotrygon venezuelae Schultz 1949 (Acevedo et al, 2015; Braccini & Chiaramonte, 2002).…”
Section: Discussionmentioning
confidence: 99%